Коммуникативно-контактные элементы как конструктивная часть композиции политической речи (на материале выступлений современных политических деятелей Франции) - Чекалина, Т.В. (Культура народов Причерноморья, 2013)
В статье представлены результаты лингвистического анализа языковых средств
контакта, применяемых оратором для активизации функции воздействия в коммуникативном процессе,
процессе взаимодействия между политиком как отправителем речи и слушателями как её
получателями.
Ключевые слова: политическая речь, коммуникативный процесс, композиционная структура,
коммуникативно-контактные элементы. В статті представлені результати лінгвістичного аналізу мовних засобів контакту, які
застосовує оратор для активізації функції впливу в комунікативному процесі, процесі взаємодії між
політиком як відправником промови та слухачами як її одержувачами.
Ключові слова: політична мова, комунікативний процес, композиційна структура, комунікативно-
контактні елементи. Using the material of public speeches of contemporary French politicians – president F. Hollande
and ex-president N.Sarcazy role of grammatical means in creating a communicative contact, fit-back connection
between public speater and his audience and some aspects of specificity of compositional structure of political
speech were analysed in the article.
The latest achivements in Teory of Communication including Political Communication , Teory of Public Speech
served as a ground for this analysis.
Based on these theoretical approaches communicative contact elements as a basic constractive part of structure
of contemporary political public speech have been discovered.
The main grammatical means in creating a communicative contact of politicain with his audience:
1) formulas of address (Mesdames, Messieurs. Chers amis, etc.)
2) personnal communicative pronouns (Je, Nous, Vous)
3) imperative mood
4) interrogative sentence
5) rhetorical question
6) specific structure – question – answer are very important for pragmatic orientation of contemporary political
speech – influencing audience.
Key words: political speech, communicative situation, compositional structure, communicative contact elements.